Antimicrobial Effect of Garlic Essential Oil (Allium sativum L.) in Combination with Chitosan Biodegradable Coating Films - E Molaee Aghaee; A Kamkar; A Akhondzadeh Basti; A Khanjari; M.G Kontominas (Institue of Medicinal Plants, ACECR, 2016)
Background: Herbal compounds like Garlic essential oil have antimicrobial and antioxidant properties. They could be effective in microbial control of inside contents when combined by natural and biodegradable coating films such as Chitosan and result in strengthened effects.  Objective: Antimicrobial effect increase by using Garlic essential oil in Chitosan film for packaging a food stuff for instance was aimed to be investigated. Methods: Chitosan film was prepared by casting method. Glycerol as plasticizer and tween80 as emulsifier were used with different levels of garlic essential oil (0, 0.5, 1 and 2%). Then homogenization and molding were performed. After packaging the food stuff with various kinds of films and storage in 4c microbial tests were conducted in days 0, 2, 4, 7, 10 and 14. Statistical analysis was performed with SPSS software. Results: Controls showed a significant difference (P≤0.05) for Total Count, Coliform, Staphylococcus aurous and Sychrotrophs when compared with samples packaged with different chitosan films. At the end of the study, Total count in those samples covered with chitosan film containing 2, 1 and 0.5 % garlic essential oil was reduced by 1.5, 1.1 and 1 log compared with control respectively. Conclusion: Garlic essential oil addition showed a significant synergistic effect in microbial inhibition with packaging by Chitosan films. Therefore, this combination could be used in future to extend the shelf life of food stuff and may also drug materials.